2016
DOI: 10.3748/wjg.v22.i8.2566
|View full text |Cite
|
Sign up to set email alerts
|

Moxibustion regulates inflammatory mediators and colonic mucosal barrier in ulcerative colitis rats

Abstract: Reduction of TNF-α and p38MAPK and increased expression of occludin and ZO-1 in colonic tissue represent a potential mechanism for improved intestinal mucosal tissue repair with grain-sized moxibustion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 27 publications
3
11
0
Order By: Relevance
“…We showed that HPM significantly downregulated the expression of IL-1β, IL-1R6, Fas and FasL, which agreed with previous studies[ 16 , 34 - 40 ]. We demonstrated that inflammatory infiltration and apoptosis in the colonic epithelium, controlled by cytokines and their network, are crucial factors in the pathogenesis of UC.…”
Section: Discussionsupporting
confidence: 93%
“…We showed that HPM significantly downregulated the expression of IL-1β, IL-1R6, Fas and FasL, which agreed with previous studies[ 16 , 34 - 40 ]. We demonstrated that inflammatory infiltration and apoptosis in the colonic epithelium, controlled by cytokines and their network, are crucial factors in the pathogenesis of UC.…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have shown that EA and moxibustion can regulate inflammatory mediators and colonic mucosal barrier in UC model rats. For instance, Ma et al found that moxibustion at CV4 and ST36 acupoints could improve intestinal mucosal tissue repair by reducing TNF-α and p38MAPK and increasing the expression of occludin and ZO-1 in colon tissues [47]. Also, EA at ST36 point could regulate the intestinal immune function by modulating IL-1β and nAchRα7 mRNA and reduce mucosal lesions to achieve the purpose of treating UC [48].…”
Section: Discussionmentioning
confidence: 99%
“…According to the equivalent dose-ratio table of human and animal body surface area: the dosage of the rats = X mg/kg × 70 kg × 0.018/0.2 kg (X is the adult clinical dosage). 23,24 The normal control (no handling) rats were classified as the NH group, NMS + RS rats were divided into 5 groups: NMS + RS; low dose group: FLWCK 1.125 mg/100 g; middle dose group: FLWCK 2.25 mg/100 g; high dose group: FLWCK 4.5 mg/100 g; and the positive control group: pinaverium bromide 1.5 mg/100 g. From postnatal day 60, the rats in the FLCWK group and positive control group were given intragastric administration with treatment, respectively; the NH group and NMS + RS group were given distilled water. All groups were treated for 14 consecutive days.…”
Section: Drugs and Administrationmentioning
confidence: 99%